In Search of Autonomy: Sexuality and the Promise of Liberation in Witold Gombrowicz’s Pornografia and Philip Roth’s Portnoy’s Complaint - Majchrowska, Oliwia (Text Matters: A Journal of Literature, Theory and Culture, 2025)
Around the launch of the Penguin series Writers from the Other Europe in 1974, Philip Roth’s novels turned to the intersections between sexuality and Jewish-American life with an increased intensity. Roth’s choice to include Witold Gombrowicz in the series invites new perspectives on the representation of collective experience and individual freedom by writers who saw their heritage not only as ill-fated but also fraught. While both authors grapple with the idea of commitment to historically disadvantaged communities, Portnoy’s Complaint and Pornografia spotlight the resistance growing in tandem with the narrators’ sexual awakening. Although writing in politically disparate contexts and almost a decade apart, Roth and Gombrowicz use the theme of sexual desire to question the impact of difficult legacies on contemporary Jewish-American and Polish life, respectively. Ultimately, the novels’ engagement with sexuality speaks to the idea of transgressing one’s foundational ties to create an autonomous self, a question relevant for both the American myth and the vexed issues of national belonging shaped by the legacy of Polish Romanticism. This article argues that Roth and Gombrowicz engage with the theme of sexual desire to create a promise of liberation, which allows them to propel the tension between the individual and the collective. Despite leading to moments of emancipation, the characters’ sexual awakening in Portnoy’s Complaint and Pornografia fails to restore their autonomy, dramatizing the novels’ images of imprisonment within the collectivity through a failed attempt to invent an autonomous self.